Effective Teams in Sport and Business. An Attempt to Use the Measurement of Entropy to Configure Sports Teams - Izabela ZIEBACZ (Communications of International Proceedings, 2021)
An approach, referring to the use of tools developed in the field of the management sciences (HRM), may introduce a new quality and perspective for designing tools and setting up effective sports teams, by building on the current knowledge of establishing employee teams. The effects of measuring and, as a consequence, shaping the potential inherent in athletes depend in some respects on the quality of management processes. This work is an attempt to present the author's method of measuring the individual potential of athletes to design an efficient sports team. This research perspective makes us see athletes from a system perspective and allows us to make conclusions about the potential of these athletes. The key term used in the empirical data processing, is entropy as understood by C.E. Shannon. Design/methodology/approach: The model presented in this work was tested on an amateur sports team (football team) in Czestochowa, Poland. Findings: In this work, we proposed the use of information entropy - which is a measure of the amount of information contained in individual competences of players. The presented method can be used to assess the competence resources at the level of a sports team. It allows, among others, to determine the distribution of competences in the group structure, to assess the fitness of the existing resource for the needs and to identify competence deficits. Practical implications: The presented concept of the method and at the same time a tool can support trainers in managing the composition of effective team formations.
Keywords: Team Effectiveness; Sport; Physical Culture; Entropy.